Pemberdayaan Masyarakat dalam Perencanaan Pasar Tradisional Terapung di Desa Bulucindea, Kecamatan Bungoro, Kabupaten Pangkajene dan Kepulauan - Imriyanti Imriyanti; Rahmi Amin Ishak; Triyatni Martosenjoyo; Syarif Beddu; M. Syavir Latif; Victor Sampebulu; Nasruddin Nasruddin; Hartawan Hartawan; Dahri Kuddu; Pratiwi Mushar (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
Bulucindea Village has the potential of mangrove forest tourism which is a coastal conservation area in Pangkajene and Kepulauan Regency (Pangkep). As part of the development of the area, three main zones were determined in the master plan, namely the zone of mangrove forests for environmental conservation, the zone of sea transportation facilities for docks, and the economic zone for traditional markets. Traditional market planning in Bulucindea Village is adapted to the physical condition of the location as a mangrove conservation area that must maintain environmental sustainability. To improve the regional economy, planning is also based on the needs of the local community. Thus the main problem of location is how to plan traditional market facilities in coastal areas that are adaptive to the environment and the economic needs of the community. Based on these considerations, community service activities are carried out, through empowerment and socialization to the community in the planning and design of traditional markets in the Bulucindea Village. The activity phase includes the analysis of problems through observing environmental conditions, and carrying out FGDs and socialization to obtain input from the community related to traditional market planning that suits community needs and the physical condition of the coastal environment of Bulucindea Village. From the community service activities, the planning concept that is considered appropriate for the coastal area of the Bulucindea Village is the concept of "Floating Traditional Market". The concept is expected to facilitate the economic activities of the community without damaging the natural habitat of the local environment, and with the community service activities it is expected that the community can take an active role in preserving the mangrove forests on the coast of the Bulucindea Village.